Iron Contamination Mechanism and Reaction Performance Research on FCC Catalyst - Zhaoyong Liu; Zhongdong Zhang; Pusheng Liu; Jianing Zhai; Chaohe Yang (Journal of Nanotechnology)
FCC (Fluid Catalytic Cracking) catalyst iron poisoning would not only influence units’ product slate; when the poisoning is serious, it could also jeopardize FCC catalysts’ fluidization in reaction-regeneration system and further cause bad influences on units’ stable operation. Under catalytic cracking reaction conditions, large amount of iron nanonodules is formed on the seriously iron contaminated catalyst due to exothermic reaction. These nodules intensify the attrition between catalyst particles and generate plenty of fines which severely influence units’ smooth running. A dense layer could be formed on the catalysts’ surface after iron contamination and the dense layer stops reactants to diffuse to inner structures of catalyst. This causes extremely negative effects on catalyst’s heavy oil conversion ability and could greatly cut down gasoline yield while increasing yields of dry gas, coke, and slurry largely. Research shows that catalyst’s reaction performance would be severely deteriorated when iron content in E-cat (equilibrium catalyst) exceeds 8000 μg/g.